2021
DOI: 10.1002/nop2.1028
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perception of medical errors: A cross‐sectional study in a university

Abstract: Unsafe practices in health facilities result in about 134 million adverse health events annually in low and middle-income countries (LMICs), contributing to about 2.6 million deaths, and one out of 10 admitted patients are victims of medical errors (MEs) associated with healthcare delivery (WHO, 2019). In nursing education, the clinical practicum is an important developmental process by which a nursing student becomes a "real nurse" (Tseng et al., 2013). Rajeswaran (2016) asserts that learning in a clinical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…This finding is consistent with Chan's study on medication errors among nursing students, whereby more than 50% (n=19) of the respondents failed the infection prevention and control category (18). Despite rigorous theoretical and practical learning opportunities on infection control during medication administration, the students continue to generate these errors, thus, compromising patient safety (20). Therefore, it is imperative to examine the knowledge of infection control and develop strategies to improve this vital aspect of medication administration.…”
Section: Infection Prevention and Control Practicessupporting
confidence: 82%
“…This finding is consistent with Chan's study on medication errors among nursing students, whereby more than 50% (n=19) of the respondents failed the infection prevention and control category (18). Despite rigorous theoretical and practical learning opportunities on infection control during medication administration, the students continue to generate these errors, thus, compromising patient safety (20). Therefore, it is imperative to examine the knowledge of infection control and develop strategies to improve this vital aspect of medication administration.…”
Section: Infection Prevention and Control Practicessupporting
confidence: 82%
“…The present study suggests that poor supervision and evaluation practice contribute to medical errors in nursing interns. In a study by Bam et al, 77% of students cited inadequate supervision in the clinical setting as a cause of medical errors [ 9 ]. Clinical training is an important part of nursing education and students can use theoretical knowledge at internship centers; therefore, supervision of this training course is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Gorgich et al show that calculating medications and prescribing medications are two areas that can lead to medical errors [ 24 ]. A study conducted in Ghana found that less knowledge of the procedure, inadequate knowledge of the medication, and workload were also associated with medication errors [ 9 ]. Students described pharmacy training programs as vulnerable and medication management skills were said to be underdeveloped [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a slew of studies investigating the use of novel approaches to teaching medicine administration in simulation have revealed that such methods are already ubiquitous. Several investigations [ 20 , 21 ] have found that employing technology such as calculators, web-based education, simulations, forums, and Virtual Learning Environments improves nurses’ knowledge and abilities in nursing operations. Despite these advancements in technology, nursing students continue to have difficulty with numerical computation.…”
Section: Introductionmentioning
confidence: 99%